Respuesta :

Answer:

OPTION C

OPTION A

OPTION C

Step-by-step explanation:

We use two - point form to determine the equation of the line when two points are given.

The two - point form is: [tex]$ \frac{y - y_1}{y_2 - y_1} = \frac{x - x_1}{x_2 - x_1} $[/tex], where [tex]$ (x_1, y_1) $[/tex] and [tex]$ (x_2, y_2) $[/tex] are the two points passing through it.

1) (x₁, y₁) = (2, 3) and (x₂, y₂) = (0, 10)

Using the two - point form, we have:

[tex]$ \frac{y - 3}{10 - 3} = \frac{x - 2}{0 - 2} $[/tex]

[tex]$ \frac{y - 3}{7} = \frac{x -2}{-2} $[/tex]

[tex]$ \implies - 2y + 6 = 7x - 14 $[/tex]

[tex]$ \implies 7x - 20 = - 2y $[/tex]

Dividing by -2, we get:

[tex]$ y = - \frac{7}{2}x + 10 $[/tex] is the equation of the line.

2) (x₁, y₁) = (1, 1) and (x₂, y₂) = (1, 5)

Using the slope - point form, we get:

[tex]$ \frac{y - 1}{5 - 1} = \frac{x - 1}{1 - 1} $[/tex]

[tex]$ \implies \frac{y - 1}{5 - 1} = \frac{x - 1}{0} $[/tex]

[tex]$ 0 = x - 1 $[/tex]

x = 1 is the required equation of the line.

3) (x₁, y₁) = (-5, 5) and (x₂, y₂) = (2, 5)

Using the slope - point form, we get:

[tex]$ \frac{y - 5}{5 - 5} = \frac{x + 5}{2 - 5} $[/tex]

[tex]$ \implies \frac{y - 5}{0} = \frac{x + 5}{-3} $[/tex]

[tex]$ \implies y - 5 = 0 $[/tex]

y = 5 is the required equation of the line.

ACCESS MORE